Risk factors for work-related musculoskeletal disorders among informal garment workers in Thailand - Chuppawa, Wipa; Thongkum, Wisit; Yoosuk, Wittaya; Tudpor, Kukiat (Intelektual Pustaka Media Utama, 2025)
Work-related musculoskeletal disorders (WRMDs), characterized by abnormalities in the musculoskeletal system, pose a significant health concern with increasing trends in illness and injuries. Informal workers are not covered by the social security scheme of insurance, preventing them from immediate healthcare services. This cross-sectional study investigated the prevalence and environmental risk factors influencing WRMDs among non-agricultural informal garment workers in Kalasin, totaling 296 individuals. Data were collected using the standardized Nordic questionnaire, descriptive statistics, and binary logistic regression. Results revealed 79.7% and 82.8% prevalence for WRMD symptoms in the past seven days and 12 months, respectively. The statistical analysis showed that improper workstations were the most influential (adjusted odds ratio (OR)=6.257, p=0.002, 95% confidence of interval (CI) [1.921, 20.388], followed by work-related stress (WRS) (adjusted OR=4.248, P=0.007, 95% CI [1.475, 12.231]. Moreover, inadequate lighting (adjusted OR=3.693, P<0.001, 95% CI [1.819, 7.497] and prolonged repetitive tasks lasting 3 5 minutes (adjusted OR=2.686, p=0.023, 95% CI [1.143, 6.309] were also contributing factors to the WRMDs symptoms. In conclusion, the prevalence of WRMDs among informal garment workers in Kalasin was high, mainly due to improper workstations and WRS.